The Rasch Analysis of Students’ Characteristics in Physics Concept Understanding Improvement through Challenge-Based Learning - Bohori, Muhammad; Liliawati, Winny; Suwarma, Irma Rahma; Ringo, Sariaman Siringo (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2022)
Concept mastery is one of the main goals in the learning process. This study aimed to analyze the improvement of students’ physics concept mastery by implementing challenge-based learning with Edmodo-assisted learning. This study used mixed methods with an embedded experimental model research design. The research sample was 10th-grade students in a public vocational school’s food crops and horticulture agribusiness program. Data analysis employed the Rasch model with the help of ministeps software version 4.1.1. The results of this study indicate a significant increase in students’ conceptual mastery of +3.44 logit. The average logit value of students’ abilities is higher than the average logit value of the item difficulty level. Students’ physics concept mastery can be improved through the challenge-based learning model assisted by Edmodo.